The verbal and the visual in language learning and teaching: insights from the 'Selfie Project'. Issue 1 (2nd January 2021) - Victoria, Mabel
ABSTRACT: That 'a picture can stimulate a thousand words' aptly summarises the role of the visual in the field of language learning and teaching. The power of the image to generate language output has been widely acknowledged in the field of second/foreign language acquisition. Posters, diagrams, symbols and pictures are often found in language classrooms; illustrations and photos cohabit with the target language in textbooks. The relationship, however, between the lingual and the visual tends to be one of asymmetry. The visual tends to be held in lower regard and thought of as 'dispensable embellishment' (Millard, E. and J. Marsh. [2001]. Words with pictures: the role of visual literacy in writing and its implication for schooling. Literacy (Formerly Reading) 35, no. 2: 54–61: 55. DOI:10.1111/1467-9345.00162) especially when the learner has acquired a certain level of linguistic competence. Instead of focusing on the 'thousand words', this initial exploration into examining the verbal–visual interplay uses the 'picture', in the form of the selfie, as heuristic device. It draws insights from visual research approaches and digital communication studies to analyse the relationship between the verbal and the visual. Results point to a counter-reading of the selfie. It is suggested that using this digital self-portrait of the twenty-first century as talking point in an English fluency exercise has brought about unexpected findings – the strengthening of personal relations in the classroom and self-reflexivity among the students – aspects that are not often associated with the traditional use of visual 'aids'. It is proposed that current understanding of the 'lingual' can be enriched by bringing the 'visual' back into the frame.